The Effects of Thermal Softening of Double-Lumen Endobronchial Tubes on Postoperative Sore Throat, Hoarseness, and vocal Cord Injuries: A Prospective, Double-blind Randomized Trial. Issue 6 (December 2016) - Seo, J.-H.; Cho, C. W.; Hong, D. M.; Jeon, Y.; Bahk, J.-H.
Abstract : (Abstracted from Br J Anaesth, 116(2):282–288, 2016) Double-lumen endobronchial tubes (DLTs) are more commonly used than single-lumen tracheal tubes for lung isolation, but tracheal intubation using DLTs is more likely to result in airway injuries or postoperative discomfort, most likely because DLTs are stiffer, have a larger external diameter, and are inserted deep into the mainstem bronchus. Thus, extra care should be taken to minimize the potential for airway injuries attendant to the use of DLTs for intubation.